Digitalization of pawnshop services and financial inclusion in Indonesia's underdeveloped, outermost, and remote regions: A systematic literature review - Wiwi Haryanti Lima; Fransina W. Ballo (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Nearly 98 million Indonesians lack formal financial access, with severe gaps in 3T regions (frontier, outermost, disadvantaged areas). Traditional banks cannot serve remote communities profitably. State-owned PT Pegadaian offers an alternative through collateral-based lending requiring no credit history, functioning as community financial infrastructure rather than purely commercial service. Digitalization initiatives mobile apps, agent networks, cloud infrastructure promise expanded reach, yet questions remain whether technology alone bridges access gaps or requires addressing infrastructure, literacy, and trust barriers. Methods: Systematic review following PRISMA 2020 guidelines analyzed 60 sources from Scopus AI searches (January 2026). Two complementary strategies identified 136 initial records; after removing 14 duplicates, 122 sources underwent systematic relevance screening using five-dimension scoring criteria. Sixty sources underwent thematic synthesis and bibliometric network analysis (VOSviewer 1.6.19). Findings: Three causal pathways emerged. The technology pathway shows digitalization contributes to broader fintech infrastructure, improving operational efficiency and service reliability. The economic pathway demonstrates digital access facilitates MSME credit acquisition and poverty reduction. The social pathway connects services to inclusion through literacy and trust, requiring complementary community-level interventions. Bibliometric analysis revealed six thematic clusters with Indonesia as central hub, but specific pawnshop mechanisms received limited scholarly attention confirming the research gap this review addresses. Conclusion: Pawnshop digitalization offers viable community service pathways but requires integrated approaches addressing infrastructure, literacy, product design, and governance simultaneously. State enterprises like Pegadaian are positioned to lead given public service mandates and extensive community networks. Novelty/Originality of this article: This is among the first systematic reviews examining pawnshop digitalization in Indonesia's 3T regions within an ESG integration framework. The dual methodology thematic synthesis and bibliometric analysis surfaces operational and socio-cultural barriers offering evidence-grounded guidance for policymakers and practitioners.